Efficient and Pure I-III-VI AIGS Quantum Dot-Based Light-Emitting Diodes via Ligand-Reshaped Surface State - Xu, Leimeng; Zhao, Jianpeng; Wang, Jindi; Yao, Jisong; Wang, Shalong; Wu, Zhi; Song, Jizhong (Nano-Micro Letters, 2026)
The I-III-VI silver indium gallium sulfide (AIGS) quantum dots (QDs) have gained extensive attention owing to their tunable emission wavelength and ecofriendly composition; however, the performance of AIGS QD-based light-emitting diodes (QLEDs) remains constrained by suboptimal surface state, significantly lagging behind that of other heavy-metal-containing QD counterparts. Herein, we propose a ligand-reshaped strategy aimed at optimizing the surface state of AIGS QDs to enhance the performance of QLEDs. A polyfunctional ligand, dimercaptosuccinic acid (DSA), is introduced to reshape the QD surface through passivation of uncoordinated Ga3+ and suppression of S vacancies. After DSA passivation, the QDs exhibit not only exceptional luminescent properties with a photoluminescence quantum yield of 89%, but also pure emission with a narrow full width at half maximum of 31 nm. Concurrently, DSA passivation markedly improves the electrical transport characteristic of QDs, thereby ensuring efficient carrier injection. Resultantly, the reshaped QLED achieves a maximum peak external quantum efficiency of 8.4% along with a narrow FWHM of 31 nm, representing a record performance reported thus far for the AIGS system. The proposed DSA ligand-reshaped strategy endows AIGS QLEDs with both high efficiency and color purity, substantially advancing their potential for the application in QD lightings and display technologies. Highlights: 1 A ligand reshaped strategy is proposed to optimize the surface state of silver indium gallium sulfide (AIGS) quantum dots (QDs) via a polyfunctional ligand, mercaptosuccinic acid. 2 Both donor–acceptor pair and non radiative recombination pathways are decreased after passivation, which leads to a notable narrowing full width at half maximum to 31 nm and an enhancement of photoluminescence quantum yield up to 89%. 3 The efficient and pure QD based light emitting diodes (QLEDs) exhibit a maximum peak external quantum efficiency of 8.4%, representing the record performance of AIGS QLEDs.